2022
DOI: 10.1038/s41467-022-35077-9
|View full text |Cite
|
Sign up to set email alerts
|

Unexpectedly efficient ion desorption of graphene-based materials

Abstract: Ion desorption is extremely challenging for adsorbents with superior performance, and widely used conventional desorption methods involve high acid or base concentrations and large consumption of reagents. Here, we experimentally demonstrate the rapid and efficient desorption of ions on magnetite-graphene oxide (M-GO) by adding low amounts of Al3+. The corresponding concentration of Al3+ used is reduced by at least a factor 250 compared to conventional desorption method. The desorption rate reaches ~97.0% for … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 49 publications
0
11
0
Order By: Relevance
“…44 Previous studies have shown that the B3LYP method and def2/SVP basis set have been widely used to explore the structure and electronic properties of graphene and GQD models. 21,45–48 All obtained local minima have positive frequencies. For the excitation transitions of GQDs, the first 20 lowest excited states were calculated using B3LYP/def2-SVP, and the solvent (water) was included based on the polarizable continuum model (PCM) 49 in the TD-DFT 29 calculations.…”
Section: Methodsmentioning
confidence: 96%
“…44 Previous studies have shown that the B3LYP method and def2/SVP basis set have been widely used to explore the structure and electronic properties of graphene and GQD models. 21,45–48 All obtained local minima have positive frequencies. For the excitation transitions of GQDs, the first 20 lowest excited states were calculated using B3LYP/def2-SVP, and the solvent (water) was included based on the polarizable continuum model (PCM) 49 in the TD-DFT 29 calculations.…”
Section: Methodsmentioning
confidence: 96%
“…Synthesis and Characterizations: Freestanding rGOMs were prepared from a GO suspension via the drop-casting and thermal reduction methods, [46][47][48][49] The rGOMs were incubated at the working electrode in a saturated NaCl solution for 1 h using a three-electrode configuration under a constant electric potential condition. Then, the rGOMs were moved to the liquid surface and crystallized by an infrared lamp for half an hour to obtain Na-Cl crystals in rGOMs at different electric potentials (Figure 1a).…”
Section: Methodsmentioning
confidence: 99%
“…This hypothesis is supported by ultraviolet (UV) absorption experiments (Figure S2). The UV spectrum of GO at ~ 230 nm is assigned to a conjugate double bond of the aromatic rings that can be generated π-π* transition [51][52][53][54][55]. The UV intensity of GO drastically decreases with the addition of Na, K, and Cs salts, but the intensity of GO with Li salt is almost identical with that from pure GO.…”
Section: Identifying Water Populations With Different Hydrogen Bondin...mentioning
confidence: 99%